Artistic and Ideological Features of Kalikhan Iskak Dramaturgy (Eurasian Journal of Philology Science and Education, 2024)
The article considers the ideological and artistic peculiarity of the plays of the Kazakh writer Kalikhan Iskak in different years published in the collections "Zharyk Duniye", "Jean Kimak". The paper analyzes such stylistic aspects of the writer's works as the creation of the image of the nature of the artistic conflict (sociological conflict, moral and philosophical, etc.), the ideological and thematic content of the works and the linguistic means of the playwright. The article focuses on interdisciplinary research. They are aimed at comprehending the nature of the conflict not only from a literary point of view, but also its sociological, philosophical and psychological facets are differentiated. In the play "When the “Geese Return”, based on the concept of the Russian literary critic T. Yesembekova, the literary and aesthetic essence of drama as a phenomenon is investigated, the relationship between native people is revealed through the psychoanalysis of Z. Freud; it is argued that the nature of the artistic conflict can be comprehended through the sociological methods of the famous researcher of the theory of social conflict L. Kozera and the literary and theoretical aspects of this conflict – from the ideological attitudes of T. Eagleton. It has been established that the conflicts in K. Iskak's play are deeply substantiated from a philosophical point of view and masterfully modeled from literary, theoretical and social points of view.It is also established that the problems of the plays of Kalihan Iskak, written in the genre of historical social drama and political satire, always go beyond the social discourse of their time, echoing the problems of today.Keywords: play, drama, conflict, historical drama, idea, problematics